El volunturismo de Muyuna Lodge y el desarrollo sostenible en la comunidad San Juan de Yanayacu 2024 - Liquerica Meza, Manuel (2025)
The final report presents as a general objective to determine the relationship between Muyuna Lodge's voluntourism and sustainable development in the San Juan de Yanayacu Community, 2024, where a basic method of descriptive and correlational level with a non-experimental design was used; opting for a sample of 68 residents, to whom a questionnaire was applied for the collection of information. The results showed that voluntourism in the San Juan de Yanayacu Community, through the participation of Muyuna Lodge, is considered regular (26%) due to its contribution in the implementation of sustainable waste management practices and the transmission of traditional knowledge in the community. However, it also mentions that Muyuna Lodge has always taken into account the needs and priorities of the community when planning community projects. Regarding sustainable development, it is rated as regular (26%). This is because it almost never participates in social and community activities organized in its locality. Furthermore, a considerable percentage of 35% never perceive that basic services such as drinking water, electricity and health are accessible and adequate in their community. Finally, there is a strong positive correlation between voluntourism at Muyuna Lodge and sustainable development, demonstrated by a coefficient of Rho=0.855 and a p value of 0.000.